Molecular characteristics and risk factor analysis of Staphylococcus aureus colonization put insight into CC1 colonization in three nursing homes in Shanghai. - Wei-Ping He (Public Library of Science (PLoS), 2021)
Research indicates that Staphylococcus aureus colonization in the elderly with predisposing risks is associated with subsequent infection. However, the molecular epidemiology and risk factors for S. aureus colonization among residents and staff in nursing homes (NHs) in China remain unclear. A multicenter study was conducted in three NHs in Shanghai between September 2019 and October 2019. We explored the prevalence, molecular epidemiology, and risk factors for S. aureus colonization. All S. aureus isolates were characterized based on antimicrobial resistance, virulence genes, multilocus sequence typing (MLST), staphylococcus protein A (spa) typing, and staphylococcal cassette chromosome mec (SCCmec) typing. NH records were examined for potential risk factors for S. aureus colonization. S. aureus and methicillin-resistant S. aureus (MRSA) isolates were detected in 109 (100 residents and 9 staff, 19.8%, 109/551) and 28 (24 residents and 4 staff, 5.1%, 28/551) subjects among 496 residents and 55 staff screened, respectively. Compared to methicillin-susceptible S. aureus isolates, all 30 MRSA isolates had higher resistance rates to most antibiotics except minocycline, rifampicin, linezolid, vancomycin, and teicoplanin. Sequence type (ST) 1 (21.3%) was the most common sequence type, and t127 (20.5%) was the most common spa type among 122 S. aureus isolates. SCCmec type I (70%) was the dominant clone among all MRSA isolates. CC1 (26/122, 21.3%) was the predominant complex clone (CC), followed by CC398 (25/122, 20.5%), CC5 (20/122, 16.4%) and CC188 (18/122, 14.8%). Female sex (OR, 1.70; 95% CI, 1.04-2.79; P = 0.036) and invasive devices (OR, 2.19; 95% CI, 1.26-3.81; P = 0.006) were independently associated with S. aureus colonization.